Rohingya Persecution in Myanmar and Thoughts on Repatriation: Evidence From Rohingya Refugee Camps in Bangladesh - Rahman, Md. Khalid; Amin, Md. Khaled (Indonesian Journal of International Law, 2024)
This study aimed to address the causes of systematic and repeated violence, extortion, torture, and persecution of Rohingya minority in Myanmar. Rohingyas were forcibly displaced from their land several times starting in 1978 to the border of Bangladesh by the Tatmadaw and the Buddhist majority. According to the United Nations (UN), within one and a half months after the exodus on 25, August 2017, Rohingyas had fled across the border, which was the largest refugee migration from Myanmar to Bangladesh. A total of 104 Rohingyas were surveyed using a structured questionnaire to investigate the causes of the mass violence. The results showed that Rohingyas were tortured, displaced, and victimized of hate crimes as a strategy to gain control over their land, and their properties including farmlands and ancestral homes were destroyed in several villages, especially in Rakhine, Kachin, and Shan states. It has also been observed that the majority of the Rohingyas were willing to voluntarily repatriate to Myanmar when the human rights conditions improve. The study contributed to the local policymakers in making policies related to Rohingya repatriation. Furthermore, it can be an important input for arranging policy dialogues or round table discussions arranged by the protagonists. The study can be extended to examine the current political and socio-economic situation in Myanmar in favour of repatriating Rohingyas to their mainland. In addition, this study contributed to the theories of Rohingya persecution, genocide, as well as safe and voluntary repatriation.